(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Academic libraries play a vital role in providing access to information and knowledge, and effective financial management is crucial for their sustainability and growth. This research assessed the current utilization of accounting information within Nigerian academic libraries and examining its impact on decision-making effectiveness. A survey research design approach was employed and data gathered was quantitatively analyzed by assessing the impact of accounting information on decision-making effectiveness in academic libraries. The research design was used because the study involved the distribution of questionnaire to selected respondents (the accounting professionals, librarians and institutions management) from six Tertiary Institutions in Nasarawa State. The study adopted the stratified sampling design in order to obtain a representative sample. The study sample size was taken by considering representation from the three major stakeholders (three each from accounting professionals, librarians and institutions management) numbering 9 for each institution given a total of 54 for all. The study variables comprise of both the dependent variable – Decision Making Effectiveness, and the Independent variable – Accounting Information. Data collected was analyzed using the descriptive statistic, correlation analysis and regression for the inferential statistics. Both the Pearson correlation and Regression analysis results corroborated the fact that accounting information significantly affects decision making effectiveness in academic Libraries in Nigeria. The study recommends among others: Training of library staff, especially those involved in financial management, on accounting principles and financial analysis; allocating financial resources to activities or projects that will yield the greatest impact on the library’s objectives; and Aligning financial goals with the overall mission and objectives of the academic library to ensure that resources are directed toward achieving the institution’s long-term vision.